Staged thermomechanical testing of nickel superalloys produced by selective laser melting. (5th November 2017) - Xu, Zhengkai; Hyde, C.J.; Thompson, A.; Leach, R.K.; Maskery, I.; Tuck, C.; Clare, A.T.
Abstract: The creep performance of additively manufactured components remains an issue before additive manufacturing can be put fully implemented. In this study, Inconel 718 two-bar specimens are produced by selective laser melting and subjected to a 'staged' creep test. Creep test was interrupted at critical junctures and X-ray computed tomography measurements performed at various extensions of the specimen. Periodic X-ray computed tomography measurements allow, for the first time, examination of the specimens during creep testing. Evaluation of specimen performance shows the number and size of pores within the specimen increasing over time as a result of classical creep mechanisms. Location and tracking over time of weak points are performed, allowing early estimation of sample failure points. This information is valuable to selective laser melting practitioners who seek to optimise the build strategy in order to minimise in-built defects. Graphical abstract: Highlights: A staged testing method is proposed to study the defects evolving during thermomechanical testing. X-ray computed tomography measurement is applied to examine the defects in a selective laser melting manufactured sample. The spatial porosity distributions and their changes during the testing become visualisation and comparable. Defect evolution during the testing also becomes visualisation and the fracture origin of the sample is accurately predicted.